2016
DOI: 10.1111/zph.12330
|View full text |Cite
|
Sign up to set email alerts
|

Sylvatic Transmission ofTrypanosoma cruziAmong Domestic and Wildlife Reservoirs in Texas,USA: A Review of the Historical Literature

Abstract: Chagas disease (Trypanosoma cruzi infection) is one of the most important neglected tropical diseases affecting the Americas. The transmission dynamic of this parasite is a complicated process that involves three genera of Triatominae subfamily and over 100 known mammalian reservoirs composed of domestic, peridomestic and wildlife species. Understanding the complex relationship between vector species and mammalian hosts is important for preventing transmission to humans. We performed a historical literature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…We reviewed all published studies of T. cruzi -infected wildlife species in the United States to tabulate parameters to input into the reservoir potential conceptual framework to evaluate the relative importance of each species (Table 1 ). In total, we reviewed 77 published estimates of anti- T. cruzi antibodies or T. cruzi parasite infection in at least 26 wildlife species across 15 southern states, expanding upon those previously reviewed across the United States ( Bern et al 2011 ) and in Texas ( Gunter et al 2016 ). In Table 1 , we combined reports of seroprevalence with direct parasite detection to calculate the overall prevalence (including seropositive animals and animals with evidence of parasite anywhere), because infection with T. cruzi is considered life-long such that hosts harboring anti- T. cruzi antibodies are also currently infected.…”
Section: Characterizing Reservoirs Of T Cruzi In mentioning
confidence: 99%
“…We reviewed all published studies of T. cruzi -infected wildlife species in the United States to tabulate parameters to input into the reservoir potential conceptual framework to evaluate the relative importance of each species (Table 1 ). In total, we reviewed 77 published estimates of anti- T. cruzi antibodies or T. cruzi parasite infection in at least 26 wildlife species across 15 southern states, expanding upon those previously reviewed across the United States ( Bern et al 2011 ) and in Texas ( Gunter et al 2016 ). In Table 1 , we combined reports of seroprevalence with direct parasite detection to calculate the overall prevalence (including seropositive animals and animals with evidence of parasite anywhere), because infection with T. cruzi is considered life-long such that hosts harboring anti- T. cruzi antibodies are also currently infected.…”
Section: Characterizing Reservoirs Of T Cruzi In mentioning
confidence: 99%
“…29 This same notion was consistent with other studies in the southern United States and it was found that various animals sustained T. cruzi transmission within the sylvatic cycle. 22 These animals included, but are not limited to, the following: armadillos, raccoons, opossums, bobcats, coyotes, and foxes. 20,24 One study revealed via a blood analysis that Trypanosoma gerstaeckeri , one of the most common species of kissing bugs in the United States, primarily feeds on nocturnal sylvatic species.…”
Section: Discussionmentioning
confidence: 99%
“…Trypanosoma cruzi , the causative agent of Chagas disease, is a vector‐borne disease transmitted to humans and a wide variety of other mammalian hosts by triatomine bugs that inhabit South and Central America, Mexico, and portions of the Southern United States . T .…”
Section: Introductionmentioning
confidence: 99%